Occurrence of Squash yellow mild mottle virus and Pepper golden mosaic virus in Potential New Hosts in Costa Rica - Castro Vásquez, Ruth Mayela (2013)
Leaf samples of Solanum lycopersicum, Capsicum annuum, Cucurbita moschata, Cucurbita pepo, Sechium edule and Erythrina spp. were collected. All samples were positive for begomoviruses using polymerase chain reaction and degenerate primers. A sequence of ~1,100 bp was obtained from the genomic component DNA-A of 14 samples. In addition, one sequence of ~580 bp corresponding to the coat protein (AV1) was obtained from a chayote (S. edule) leaf sample. The presence of Squash yellow mild mottle virus (SYMMoV) and Pepper golden mosaic virus (PepGMV) were confirmed. The host range reported for SYMMoV includes species of the Cucurbitaceae, Caricaceae and Fabaceae families. This report extends the host range of SYMMoV to include the Solanaceae family, and extends the host range of PepGMV to include C. moschata, C. pepo and the Fabaceae Erythrina spp. This is the first report of a begomovirus (PepGMV) infecting chayote in the Western Hemisphere.